2007
DOI: 10.1007/s00383-006-1848-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered regulation of retinoic acid synthesis in nitrofen-induced hypoplastic lung

Abstract: Retinoids are a group of molecules derived from vitamin A, which play an important role in lung development. Within the cell, retinol can either be oxidized to retinal or esterified to retinyl esters by lecithin : retinol acyltransferase (LRAT) for storage. Retinal is then oxidized to an active metabolite of vitamin A, retinoic acid (RA) by retinal dehydrogenase (RALDH). RA is the active metabolite of vitamin A. Cyp26 (a1,b1, and c1), which is a member of the cytochrome P450 family, acts by reducing the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 24 publications
(30 reference statements)
3
28
0
Order By: Relevance
“…Recently, Nakazawa et al [79] studied the effects of nitrofen on the retinoid-signaling pathway in hypoplastic lungs. They demonstrated that LRAT was downregulated, causing a shift of retinol from storage to conversion in RA.…”
Section: Cdh-associated Chromosomal Hot Spots and Candidate Genes Invmentioning
confidence: 99%
“…Recently, Nakazawa et al [79] studied the effects of nitrofen on the retinoid-signaling pathway in hypoplastic lungs. They demonstrated that LRAT was downregulated, causing a shift of retinol from storage to conversion in RA.…”
Section: Cdh-associated Chromosomal Hot Spots and Candidate Genes Invmentioning
confidence: 99%
“…In the nitrofen model, coadministration of large doses of vitamin A reduces the incidence of CDH and attenuates lung hypoplasia [26]. Furthermore, nitrofen has been reported to inhibit retinal dehydrogenase (RALDH-2) [42], the major retinoic acid synthesizing enzyme, whereas other studies have shown a downregulation of Cyp26b1 (a cytochrome P450 that reduces the activity of retinoic acid) and LRAT (lecithinretinol transferase that esterifies retinol to retinyl esters for storage) [27,28]. In the current study, we have found a decrease of RARα after nitrofen.…”
Section: Discussionmentioning
confidence: 97%
“…An increased expression of matrix metalloproteinase 9 (MMP-9) has been reported [24], as well as an alteration of the retinoid acid pathway at different levels [25][26][27][28]. The lungs of rodents with nitrofen-induced CDH have also been shown to have increased expression of intercellular adhesion molecule 1 and vascular cell adhesion molecule 1 [29], increased angiotensin-converting enzyme activity [30], decreased endothelial isoform of nitric oxide synthase (eNOS) expression [31], increased endothelin-1 and endothelin A vasoconstrictor receptor [32], and altered K + channel expression [33], which might contribute to increased pulmonary vascular tone in the teratogenic model of CDH.…”
mentioning
confidence: 99%
“…Previous study from our laboratory has shown that gene expression of FGF-7 and FGF-10 is downregulated in the nitrofeninduced hypoplastic lung [13]. Furthermore, retinoids, which can also activate PI3K, has been reported to be involved in pathogenesis of CDH and associated pulmonary hypoplasia, and recent studies have also suggested that the retinoid signaling pathway (RSP) is inhibited in the nitrofen-induced hypoplastic lung [14][15][16][17]. However, the relationship between PI3K-AKT signaling pathway and lung hypoplasia associated with CDH has not been elucidated.…”
mentioning
confidence: 92%